Strategi Badan Permusyawaratan Desa (BPD) dalam Pengawasan Tata Kelola Pemerintahan di Desa Sepit Kecamatan Keruak Kabupaten Lombok Timur - Samsul Hadi; Muh. Wahyunadi; Hairul Izwan; Alwi Sahri Ramadhani (Pendidikan Al-Gafari, 2024)
Villages are the seeds of the formation of a country, not only in Indonesia but throughout the country. But ironically, the development of rural areas in Indonesia is always marginalized, public services at the village level are the worst level of service among public services in Indonesia. The purpose of this study is to 1) find out the planning of BPD in supervising governance in Sepit village, 2) find out how the implementation of BPD strategy in supervising governance in Sepit village, and 3) find out how the obstacles of BPD in supervising governance in Sepit village. This study highlights the importance of a strong understanding of the roles and responsibilities of BPD in supervision. In addition, an effective strategy requires an efficient understanding of resources, independence from political interference, increased access to information, and the development of networks and cooperation. By implementing these strategies, BPD can strengthen its role in improving transparency, accountability, and quality of governance at the village level. The implications of this study can provide practical guidance for BPD and related parties in strengthening the supervision mechanism at the village level.